2011
DOI: 10.1111/j.1745-4530.2009.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Process Parameters Using Response Surface Methodology on the Quality of Crustless Bread Baked in a Water‐spraying Oven

Abstract: A special type of water‐spraying oven was developed where crustless bread was prepared by gently baking the dough at different combinations of baking temperature and baking time, and spraying water at prefixed intervals on the surface of the dough. Response surface methodology was used to investigate the influence of predictor variables on bread quality in terms of surface moisture, bottom moisture, color value in terms of L*, b*and softness in terms of cutting force. In the study, each predictor variable was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Afterwards the rate of browning might get reduced due to less availability of water and substrates. A modification in lightness value for the expanded loaf might also serve as one of the reasons for this type of behavior (Mondal & Datta, ; Purlis, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Afterwards the rate of browning might get reduced due to less availability of water and substrates. A modification in lightness value for the expanded loaf might also serve as one of the reasons for this type of behavior (Mondal & Datta, ; Purlis, ).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the linear model, the quadratic models are flexible and can provide a good approximation to the developed response surfaces as these models consider the linear, square, and interaction dependence of the responses on the factors (Bezerra, Santelli, Oliveira, Villar, & Escaleira, ). Furthermore, several studies have also reported that second‐order models are able to explain the trends in the responses such as texture, color, and volume of bread during the baking process (Mondal & Datta, ; Sevimli et al, ). In this sense, a quadratic polynomial model (Equation 10) was developed for each response as a function of independent variables viz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… dureza para > t e baixas T Izadi Najafabadi et al 2014Pão sem crosta T: 160, 170, 180°C; t: 25, 30 e 35 min; Vapor: 6, 8 e 10 min todos influenciam a força de cisalhamento. Datta (2011) Pão de mandioca T: 190 a 240°C; t: 20 a 40 min.  t = > dureza.…”
Section: Propriedades Físicasunclassified